Sesame Oil (Sesamum Indicum L.) as a New Challenge for Reinforcement of Conventional Glass Ionomer Cement, Could It Be? - Neven S. Aref (International Journal of Dentistry)
Purpose. Despite the advantages of glass ionomer cement (GIC) including chemical bonding to the tooth structure and fluoride release, its low-grade mechanical properties make it a topic for research. Accordingly, this study was conducted to assess the ability of sesame oil as a natural bioactive additive to reinforce conventional glass ionomer cement. Materials and Methods. Sesame oil was blended into the liquid component of the cement in ratios of 3 and 5 (v/v%). One control and two experimental groups were enrolled in the study; I: unmodified GIC (control), II: 3 (v/v%) sesame oil-modified GICs, and III: 5(v/v%) sesame oil-modified GICs. Compressive strength, shear bond strength, diametral tensile strength, surface microhardness, surface roughness, and color stability were the parameters assessed. A representative specimen of each group was analyzed for its chemical structure by Fourier transformation infrared spectroscopy. One-way ANOVA followed by Tukey test was used to analyze the collected data of all evaluated parameters except the color stability results, which were analyzed by Student t-test at p<0.05. Results. Three and 5 (v/v%) sesame oil-modified GICs exhibited significant increase in their compressive strength, shear bond strength, diametral strength, and surface microhardness. Concurrently, there was a significant decrease in surface roughness (p<0.05) in both formulations of the modified cement. Both 3 and 5 (v/v%) sesame oil-modified GICs showed a clinically acceptable color change. Conclusions. Sesame oil seems to be a promising natural bioactive product for reinforcement of conventional GIC with a clinically agreeable esthetic.